Business Model Analysis On Project X Event Organizer With Business Model Canvas Approach - Putra, Muhamad Singgih Farizki; Fitria, Siska Eka; Hatammimi, Jurry (eProceedings of Management, 2024)
Project X event organizer is a company engaged in the event organizer. Event organizer Project X is an event organizercompany focusing on entertainment. Event organizer Project X was founded on November 20, 2019, to createunforgettable experiences. Through events focusing on the central concept of space adventure as a platform for everyoccasion, Project X also provides entertainment through Disc Jockey, both resident/non-residents. This study's resultscontribute to business strategy research by using Business Model Canvas to analyze and map strategies. The results of thisstudy can be used as a reference for further research and add insight into the business model canvas. The research methodused is a descriptive qualitative method. The primary data collection technique uses semi-structured interviews. Theresearch results show that Project X needs for regional expansion, taking human resources from outside for the company'sprogress, choosing the same place but developing a broader theme, and taking other genres to be able to compete betterwith more robust competitors. The suggestions for Project X Event Organizer is can maximize the factors that have beenprovided by researchers by improving or utilizing them in running their business.Keywords-business model analysis, business model canvas, SWOT